2019
DOI: 10.1017/s0016756819001316
|View full text |Cite
|
Sign up to set email alerts
|

Finding the VOICE: organic carbon isotope chemostratigraphy of Late Jurassic – Early Cretaceous Arctic Canada

Abstract: A new carbon isotope record for two high-latitude sedimentary successions that span the Jurassic–Cretaceous boundary interval in the Sverdrup Basin of Arctic Canada is presented. This study, combined with other published Arctic data, shows a large negative isotopic excursion of organic carbon (δ13Corg) of 4‰ (V-PDB) and to a minimum of −30.7‰ in the probable middle Volgian Stage. This is followed by a return to less negative values of c. −27‰. A smaller positive excursion in the Valanginian Stage of c. 2‰, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 98 publications
1
36
0
Order By: Relevance
“…Two further Berriasian ammonite horizons, characterised by the occurrence of Borealites fedorovi and Pseudocraspedites anglicus, respectively, were documented (Jeletzky, 1984; see also Galloway et al, 2020). Rich Valanginian macrofossil assemblages are restricted to the Deer Bay Formation in the central part of the Sverdrup Basin, and mostly recorded from Amund Ringnes and Ellef Ringnes islands.…”
Section: Biostratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…Two further Berriasian ammonite horizons, characterised by the occurrence of Borealites fedorovi and Pseudocraspedites anglicus, respectively, were documented (Jeletzky, 1984; see also Galloway et al, 2020). Rich Valanginian macrofossil assemblages are restricted to the Deer Bay Formation in the central part of the Sverdrup Basin, and mostly recorded from Amund Ringnes and Ellef Ringnes islands.…”
Section: Biostratigraphymentioning
confidence: 99%
“…Logically, one would turn to high latitude records when searching for evidence of cold snaps and ice caps, or more generally for an archive of pronounced climate fluctuations. The Mesozoic sedimentary succession of the Sverdrup Basin in Arctic Canada is one of the best candidates for investigating these topics (Kemper 1987;Galloway et al, 2020). Today, only the Wandel Sea Basin in northern Greenland has exposures of the Jurassic-Cretaceous boundary interval that lie at a higher latitude (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although some attempts at chemostratigraphic correlation of these rocks were undertaken recently (Turner et al 2019), deposition of high-latitude Upper Jurassiclowermost Cretaceous black shales are not associated with any significant carbon isotope excursions. The only carbon isotope excursion during middle Volgian time, the so-called VOICE (Volgian Isotopic Carbon Excursion), can be recognized in some Boreal areas (Hammer et al 2012;Koevoets et al 2016;Galloway et al 2019); in contrast to excursions related to the typical OAEs it is relatively long, spanning nearly the whole middle Volgian age, and showing some diachroneity between the basins. The onset of black shale deposition was strongly asynchronous in the different basins and even different sub-basins, and the same is also true for the termination of black shale deposition with the end of the SDAE.…”
Section: Key Features Of the Late Jurassicearliest Cretaceous High-lamentioning
confidence: 99%
“…Highest TOC values are reported from the Kimmeridgian part of the succession (Gentzis et al 1996), while the Volgian-Ryazanian interval is characterized by less than 5% of TOC. Recent data by Galloway et al (2019) have revealed that the Deer Bay Formation of the Axel Heiberg island is generally characterized by low TOC values throughout the succession. Their two measured sections show median values of TOC 1.6%, with range 0.9-4.6% (Buchanan Lake section) and TOC 1.8%, with range 0.8-5.7% (Geodetic Hills section).…”
mentioning
confidence: 99%
“…This debate can only be resolved by adding more high-resolution multi-proxy data from high-latitude archives. Galloway et al (2019) present detailed C-isotope records integrated with ammonite biostratigraphy from Axel Heiberg Island, in the high Canadian Arctic. They improve the chronostratigraphy for the uppermost Jurassic and lowermost Cretaceous interval, a problematic time interval in need of chronological refinement.…”
mentioning
confidence: 99%